Development of Autonomous Follow-me Robot, Robot Tool Cart Version 2 for Education - Ismail, Norisza Dalila; Misnadi, Harith Iskandar; Muchtar, Muhamad Hilmi; Noor Azri, Muhammad Haiqal; Mat Johan, Muhammad Akmal (Multidisciplinary Applied Research and Innovation, 2021)
The Robot Tool Cart Version 2 (RTCV2) is designed based on a normal tool cart which is used to store the tools, equipment and some documents in the tool crib. Nowadays, the tool cart used in a hangar is non-autonomous technology, so a manpower is needed to push the tool cart to the workspace or back to the tool crib. This is of course a problem as it would exhaust the worker even before they need to do the task given to them. So, our project is to improve the normal tool cart with some features consists of IR4.0 technology which is Robotic features and Autonomous Technology. This product function is to follow the user to the desired location within the hangar area by using the Follow-me programme installed inside the Arduino that is used on the Robot Tool Cart Version 2 (RTCV2). Other than that, it will also keep the function as a normal tool cart, which is to keep all the tool, equipment and also document for the user to access either at the workspace or at the tool crib. The Robot Tool Cart Version 2 (RTCV2) is also an easy to operate technology where the user will only needed to control the the ON and OFF switch to operate it and shut it down. The Robot Tool Cart Version 2 (RTCV2) is also an easy maintenance product as it has an easy access to the wiring if there is maintenance needed to be done on the product. With all the function above this will surely ease the user to do their work/task efficiently. As it will decrease the amount of manpower needed just to push the tool cart to the workspace or back to the tool crib.